R&D&C efforts of forest herbals obtained from indigenous people into NPRA approved commercial capsules - Vejayan, Jaya; Yusoff, M. M.; Mohamed, Aini Norhidayah (2019)
This study was initiated as UMP-community technology solution platform with a grant bearing number: UIC170904. The technology is the R&D&C efforts by a small group of university researchers in assisting the community of the indigenous people at Kampung Bukit Cermin, Perak. Based on the feedback given by the indigenous community an herbal product compromising mixture of three Tongkat Ali plants been selected and worked upon. It is believed by Malay and indigenous traditional practitioners that all three types of Tongkat Ali have aphrodisiac properties. Eurycoma longifolia or known as Tongkat Ali is widely known for their aphrodisiac properties. However, many researchers only focused on Tongkat Ali Putih to be proven with aphrodisiac properties with less or absolutely no emphasis to Tongkat Ali Hitam and Merah. This study provides some account on the procedures of utilizing a contract manufacturer, TPM Biotech Sdn Bhd, in registering the product with NPRA. R&D on the three plants were concurrently done and established the presence of protein within them. Up to now, the compounds that responsible for its aphrodisiac properties not yet studied. Glycoprotein was suspected to be the protein that responsible for the aphrodisiac capabilities in enhancing testosterone in male. This study is to detect the presence of protein in all three types of Tongkat Ali crude extracts. SDS PAGE analysis showed the presence of protein bands in all three types of Tongkat Ali crude extracts. The protein content in Tongkat Ali Putih, Hitam and Merah were calculated by Bradford Assay analysis as 0.61 w/w %, 1.67 w/w % and 2.01 w/w % respectively. Also investigated was the aphrodisiac efficacy and the safety of the plants in fowls. The blood samples of the chicken were collected and send to a Diagnostic Laboratory in Kuantan, Pahang to be evaluated. The result shown that chicken that consumed Tongkat Ali Putih have the highest testosterone level compared to others. Tongkat Ali Merah ranked second while Tongkat Ali Hitam results were in doubt and required repeat. Additional test was also conducted which were the important safety biomarkers for liver. The result indicated that there were mild damages on the liver biomarkers of the chicken by Tongkat Ali Putih with the other types of Tongkat Ali found to be at safe levels. Besides that, four different sexual mating behavior observations conducted shown with positive sexual mating activities on all chicken tested. Chicken that consume Tongkat Ali Putih have the highest frequency of sexual mating activity compare to others. While chicken that consumed Tongkat Ali Merah and Hitam have a somewhat similar frequency of sexual mating activities. The overall analysis showed that Tongkat Ali Putih can be ranked first with the most positive aphrodisiac properties followed with Tongkat Ali Merah and lastly Tongkat Ali Hitam (pending a repeat on its in vivo investigation). It was also concluded due to higher dose used i.e. 12mg of the Tongkat Ali Putih per capsule, it is likely provided some acute safety issues and hence required lowering of this dose in order to assess further in the chronic studies (more than 6 months). In overall conclusion, the study provided an example of an initiative to develop herbal product with the efforts provided by the indigenous people, researchers and industry. This can be useful platform for other researchers to mimic in developing more such products from the rich Malaysian biodiversity.